Incidence and pattern of mandibular fractures in Rohilkhand region, Uttar Pradesh state, India: A retrospective study - Kolli Yada Giri; Aishwarya Pratap Singh; Ramakant Dandriyal; Niranjanaprasad Indra; Sanjay Rastogi; Sunil Kumar Mall; Shouvik Chowdhury; Himanshu Pratap Singh (Journal of Oral Biology and Craniofacial Research)
Aims: To understand and evaluate the significance of various aetiological factors in determining the incidence and dictating the patterns of mandibular fractures in Rohilkhand region. Methods: The patient records and radiographs for 144 patients treated for mandibular fractures were reviewed between the time periods from January 2012 to December 2013. Data on age, gender, aetiology, use of intoxicants, head injury, associated injuries, days of the week, anatomic site and multiple fractures within the mandible were recorded and assessed. Results: Maximum incidence of fractures was observed among the individuals in 3rd decade (35.4%) followed by 2nd and 4th decades, which exhibited 32 and 30 cases (22.2% and 20.8%), respectively. Male to female ratio was biased (4:1) portraying a male predominance. Road traffic accidents (RTAs) were observed to be the predominant aetiological factor responsible accounting for 79.2% of the total injuries followed by assaults (11.8%) and falls (9%). Parasymphysis exhibited the highest incidence (32.63%) amongst the anatomic sites, followed by body (18.75%), angle (16.66%), condyle (15.27%), symphysis (12.50%), ramus (2.77%) and coronoid (1.38%). Conclusion: The study reveals that majority of affected patients were in the 2nd and 3rd decades. A definitive relationship existed between RTA and the incidence of mandibular fractures. The frequency further increased with consumption of social intoxicants. The most commonly fractured site was parasymphysis either isolated or associated with other fractures in the mandible.